Respuesta :
Answer:
Step-by-step explanation:
Rule Example
+(+) Two like signs become a positive sign 3+(+2) = 3 + 2 = 5
−(−) 6−(−3) = 6 + 3 = 9
+(−) Two unlike signs become a negative sign 7+(−2) = 7 − 2 = 5
−(+) 8−(+2) = 8 − 2 = 6
When you add two positives it’s a positive
When you add a positive and negative it’s either depending on each number
When you add two negatives the answer will be negative -3+(-4)=-7
When you add a positive and negative it’s either depending on each number
When you add two negatives the answer will be negative -3+(-4)=-7